Preliminary Study on Changes of Sleep EEG Power and Plasma Melatonin in Male Patients With Major Depressive Disorder After 8 Weeks Treatment - Wang, Xue-Qin; Wang, De-Quan; Bao, Yan-Ping; Liu, Jia-Jia; Chen, Jie; Wu, Shao-Wei; Luk, Hsuan-Nu; Yu, Ling; Sun, Wei; Yang, Yong; Wang, Xue-Hua; Lu, Lin; et al. (Frontiers in Psychiatry, 2021)
Objective: To clarify the effects of escitalopram on sleep EEG power in patients with MDD. Method: Polysomnography (PSG) was detected overnight, and blood samples were collected at 4 h intervals over 24 h from 13 male healthy controls and 13 male MDD patients before and after treatment with escitalopram for 8 weeks. The outcome measures included plasma melatonin levels, sleep architecture, and the sleep EEG power ratio. Results: Compared with healthy controls, MDD patients presented abnormalities in the diurnal rhythm of melatonin secretion, including peak phase delayed 3 h and a decrease in plasma melatonin levels at night and an increase in daytime, accompanied by sleep disturbances, a decrease in low-frequency bands and an increase in high-frequency bands, and the dominant right-side brain activity. Several of these abnormalities (abnormalities in the diurnal rhythm of melatonin secretion, partial sleep architecture parameters) persisted for the 8-week testing period. Conclusions: Eight weeks of treatment with escitalopram significantly improved depressed patients’ subjective sleep perception and depressive symptoms, and partially improved objective sleep monitoring parameters, while the improvement of circadian rhythm of melatonin was limited.